Radical oxygen species production induced by advanced oxidation protein products predicts clinical evolution and response to treatment in systemic sclerosis. Issue 9 (15th March 2007) - Servettaz, A; Guilpain, P; Goulvestre, C; Chéreau, C; Hercend, C; Nicco, C; Guillevin, L; Weill, B; Mouthon, L; Batteux, F
Abstract : Objectives: To investigate the role of reactive oxygen species (ROS) in the development of the various patterns of systemic sclerosis (SSc) and the mechanisms of ROS production by endothelial cells and fibroblasts. Methods: Production of hydrogen peroxide (H2 O2 ), nitric oxide (NO) and cellular proliferation were determined following incubation of endothelial cells and fibroblasts with 56 SSc and 30 healthy sera. Correlations were established between those markers, the type and the severity of the clinical involvements, and the response to treatment. The factors leading to ROS production were determined. Results: H2 O2 production by endothelial cells and fibroblasts was higher after incubation with SSc sera than with normal sera (p<0.001) and with sera from SSc patients with severe complications than sera from other patients (p<0.05). Sera from patients with lung fibrosis triggered the proliferation of fibroblasts more than other SSc sera (p<0.001), whereas sera from patients with vascular complications exerted no proliferative effect on fibroblasts, but inhibited endothelial cell growth (p<0.05) and induced NO overproduction (p<0.05). Bosentan reduced NO release by 32%, whereas N-acetylcystein potentiated 5-fluorouracil (5FU) to inhibit fibroblast proliferation by 78%. Those serum-mediated effects did not involve antibodies but advanced oxidation protein products that selectively triggered cells to produce H2 O2 or NO. Conclusions: SSc sera induce the production of different types of ROS that selectively activate endothelial cells or fibroblasts, leading to vascular or fibrotic complications. Assaying serum-induced ROS production allows clinical activity of the disease to be followed and appropriate treatments to be selected.